PRIORITIES OF EDUCATIONAL SYSTEM TECHNOLOGY - Gozalkhon Mahmudovna Yakubova (University Research Base, 2024)
In the early 1960s, the organization of the educational process based on the programming of education began to be seen as a factor in revealing the essence of the concept of “technology”. Program education is the process of imparting specific knowledge to children in a coherent, holistic way, rather than as a separate part. This article outlines the priorities for technology in education.